Strategic content marketing: Creating effective content in practice - Farkas, Dan; Geier, Rebecca (London Routledge, 2024)
Strategic Content Marketing offers a comprehensive guide to plan, create, implement and analyse an effective content marketing strategy in practice. Each chapter marries established theory with modern practice, illustrating concepts with real-world case studies and examples, alongside interviews with prominent content marketers, including a foreword by Joe Pulizzi, founder of The Content Marketing Institute and often referred to as the Father of Content Marketing. Chapter objectives and summaries structure learning, whilst reflective questions and activities aid comprehension. On reading, students will understand: The definition, purpose and practical implementation of a content marketing programme The relationship between content marketing and broader marketing, strategic positioning, buyer personas, and research initiatives The most effective and valued forms of content marketing, how they are structured and used, including a special focus on digital and B2B content marketing How to create persuasive content and measure the effectiveness of content marketing The careers, associated competencies, and software technologies in the burgeoning field of content marketing. This comprehensive text is perfect core and recommended reading for advanced undergraduate and postgraduate students studying Content Marketing, Inbound Marketing, Marketing Communications, Digital and Social Media Marketing and Public Relations. In practice, the book is also highly valuable for practising professionals studying for professional qualifications and looking to develop their skills. Online resources include instructor teaching slides, four-color images and templates, and chapter test bank questions.
Keywords: Marketing; Internet marketing; Content marketing